Expression characteristics of ARF1 and SAR1 during development and the de-etiolation process - Keskin, B. Cevher; Yuca, E.; Ertekin, O.; Yuksel, B.; Memon, A. R. (WILEY, 2012)
ARF1 (ADP-ribosylation factor 1) and SAR1 (secretion-associated RAS super family) are involved in the formation and budding of vesicles throughout plant endomembrane systems. The molecular mechanisms of this transport have been studied extensively in mammalian and yeast cells. However, very little is known about the mechanisms of coat protein complex (COP) formation and recruitment of COP-vesicle cargoes in plants. To provide insights into vesicular trafficking in Pisum sativum L., we investigated mRNA and protein expression patterns of ARF1 and SAR1 in roots and shoots at early growth stages and in the de-etiolation process. We showed that ARF1 was concentrated mostly in the crude Golgi fractions, and SAR1 was concentrated predominantly in the crude ER fractions of de-etiolated shoots. ARF1 and SAR1 proteins were several times more abundant in shoots relative to roots. In total protein homogenates, the expression level of SAR1 and ARF1 was higher in shoots of dark-grown pea plants than light-grown plants. In contrast, ARF1 was higher in roots of light-grown pea relative to roots of dark-grown pea. With ageing, the ARF1 mRNA in roots was reduced, while SAR1 expression increased. Unlike ARF1 transcripts, ARF1 protein levels did not fluctuate significantly in root and shoot tissue during early development. The relative abundance of SAR1 protein in root tissues may suggest a high level of vesicular transport from the ER to the Golgi. Experimental results suggested that white light probably affects the regulation of ARF1 and SAR1 protein levels. On the other hand, short-term white light affects SAR1 but not ARF1.
Keywords: COP-vesicle cargo; de-etiolation; GTP-binding proteins; quantitative real-time RT-PCR; vesicular trafficking; ADP-RIBOSYLATION FACTOR; GTP-BINDING PROTEIN; ENDOPLASMIC-RETICULUM; ROOT HAIRS; DISSOCIATION INHIBITOR; REGULATED EXPRESSION; VESICLE TRAFFICKING; GENOME EXPRESSION; POLARIZED GROWTH; SMALL GTPASES; Plant Sciences